ANALISIS PENERAPAN E-FAKTUR DALAM PELAPORAN PAJAK PERTAMBAHAN NILAI (PPN) PADA PT INS GENERAL INDONESIA SURABAYA - Ainurrahma Nurul Achdiyati; Heru Tjahjono (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
The purpose of this research is to analysis e-invoice’s use on VAT Reporting on PT INS General Indonesia. This research use primary and secondary data by qualitative approach. The result of this research is that PT INS General Indonesia has used e-invoice properly especially on the newest version 3.2 which is suitable with regulation of Directorate General of Taxes PER-03/PJ/2022. In other that, PT INS General Indonesia does properly article 18 paragraph 1 regulation of the Directorate General of Taxes which is uploading a tax invoice before or on 15th of the next month. However in the use of e-invoice, The Directorate General of Taxes needs to optimalize server to be accesed by the user simply and optimalization the benefit of prepopulated data income tax on PT INS General Indonesia.